Where is the Amazon? - Fabiny, Sarah (Where is (Grosset & Dunlap), 2016)
"Without risking life or limb, readers can explore the wonders and beauty of the Amazon in this Where Is ...? title. Human beings have inhabited the banks of the Amazon River since 13,000 BC and yet they make up just a small percentage of the 'population' of this geographic wonderland. The Amazon River basin teems with life--animal and plant alike. It's a rainforest that is home to an estimated 390 billion individual trees, 2.5 million species of insects, and hundreds of amazing creatures and plants that can either cure diseases, or, like the poison dart frog, kill with a single touch. Where Is the Amazon? reveals the amazing scale of a single rainforest that we are still trying to understand today and that, in many ways, supports our existence on this planet"--